Cyclosporin A-induced gingival overgrowth is not associated with myofibroblast transdifferentiation - Lays Martin Sobral; Michele Gassen Kellermann; Edgard Graner; Hercilio Martelli-Junior; Ricardo Della Coletta (Sociedade Brasileira de Pesquisa Odontológica, 2010)
Cyclosporin A (CyA) induces gingival overgrowth via its stimulatory effects on expression of transforming growth factor-beta1 (TGF-β1) and collagen. It is not known whether CyA has a direct effect on gingival fibroblasts or induces its effect indirectly via stimulation of myofibroblast transdifferentiation. The present study was undertaken to examine the in vivo and in vitro effect of CyA on myofibroblast transdifferentiation. Rats were treated for 60 days with a daily subcutaneous injection of CyA, and the gingival overgrowth tissue was analyzed by immunohistochemistry. In vitro, fibroblasts from normal gingiva (NG) were cultured in the presence of different concentrations of CyA, and subjected to semi-quantitative reverse transcriptase-polymerase chain reaction and western blot. Although CyA treatment stimulated TGF-β1 expression by NG fibroblasts, it lacked to induce expression and production of isoform α of smooth muscle actin (α-SMA), the specific myofibroblast marker. The expression levels of connective tissue growth factor (CTGF), which has been considered a key molecule to promote the transdifferentiation of myofibroblasts via TGF-β1 activation, were unaffected by CyA. Our results demonstrate that CyA-induced gingival overgrowth is not associated with activation of myofibroblast transdifferentiation, since CyA is not capable to increase CTGF expression.